Advancing Epigenetic and Antioxidant Strategies in Natural Therapeutics Against SARS-CoV-2: A Mini Review of Current Innovations and Future Directions - Adrianta, Ketut Agus; Wibawa, Agung Ari Chandra; Siada, Nyoman Budiartha; Suena, Ni Made Dharma Shantini; Wardani, I.G.A.A Kusuma (Natural Products Journal, The, 2025)
This review explores the potential of natural products, particularly curcumin and gingerol, as immune regulators and anti-inflammatory agents in combating SARS-CoV-2 infections via epigenetic and antioxidant mechanisms. Oxidative stress induced by coronavirus infections can trigger severe immune responses, such as cytokine storms, often leading to therapy failure. This oxidative stress is exacerbated by depleted antioxidant defenses. The review examines how natural ingredients activate endogenous antioxidants through pathways like nuclear factor erythroid 2-related factor 2 (Nrf-2) activation, leading to gene expression changes without altering DNA structure. These changes enhance cellular defenses against oxidative stress and reduce inflammation, potentially mitigating the virus's effects. The methodology involved a literature review of scientific articles from databases such as Google Scholar, Elsevier, Science Direct, Scopus, and Wiley Online Library, focusing on publications from 2010 to 2023. Data were analyzed using deductive qualitative descriptive techniques, emphasizing the role of natural compounds in activating antioxidant responses to prevent or minimize cellular damage caused by COVID-19. The review underscores the significant role of diet and nutritional intake in supporting the body's antioxidant capacity by activating specific receptors that influence gene expression related to immune responses and cellular repair mechanisms. Flavonoids and anthocyanins are highlighted as key compounds in natural products with therapeutic potential against COVID-19. Overall, this research advocates for further exploration of natural products as viable options for preventing and treating COVID-19, suggesting that these compounds offer dual benefits of antiviral activity and immune modulation through epigenetic regulation and antioxidant support.
Keywords: natural products